Technical High Level and Undergraduate Courses: Comparison of vacancies and new entrants at the Federal Institute of Amapá, Brazil (2017-2018) (Research, Society and Development, 2020)
The Federal Institute of Amapá (IFAP) is an autonomous educational institution with a multi-camp structure. It has academic performance areas such as the Initial and Continuing Education (FIC) or Professional Qualification courses; the technical courses of medium level, covering the integrated form, subsequent form and the modality of Youth and Adult Education (EJA), Undergraduate and Graduate Lato Sensu and Stricto Sensu. The objective of this work is to make a comparison of vacancies and new entrants at the Federal Institute of Amapá in high school and undergraduate courses between the years 2017 to 2018. The research has a quantitative and qualitative approach, and was carried out based on the data informed by the Nilo Peçanha Platform, as well as bibliographic research on the most current academic productions, related to the theme of the article. As well as, the investigation resulted in a demonstration of the increase in high school entrance and vacancies, when compared to the same level of entrance of the Higher Education courses in the year 2018. In addition, it demonstrated the increase in the offer of Technical Vocational Education at Level Medium in the subsequent modality to the detriment of the integrated modality; he also assessed and concluded that the Macapá Campus (capital) remains undefeated with the largest number of entrants. However, it presented a decay from 2017 to 2018 and finally, it showed that IFAP presented a greater number of new students for technology courses.